Recent Advances in Drug Addiction Research and Clinical Applications - Meil, William M.; Ruby, Christina L. (IntechOpen, 2016)
Although it is well-accepted that drug addiction is a major public health concern, how we address it as a society continues to evolve as recent advances in the lab and clinic clarify the nature of the problem and influence our views. This unique collection of eight chapters reviews key findings on the neurobiology and therapeutics of addiction while capturing the diversity of perspectives that shape these concepts, which range from evolutionary biology to psychiatry to the legal system. This book discusses in depth how technological advances have led to important discoveries and how these discoveries, in turn, are increasingly being translated into clinical practice. It also presents avenues for future study that hold promise for the many affected by addiction.